Pharmacological methods of pain relief during labor - Michalczyk, Michał; Torbé, Dorota; Torbé, Andrzej (Journal of Education, Health and Sport, 2018)
Labor pain and methods of its alleviation constitute the main problem in contemporary obstetrics, both for the patients themselves, as well as for the medical staff. Concerns associated with pain are not meaningless to the course of labor, are inextricably linked to the quality of perinatal care and to a large extent affect the costs of functioning of the health care system. Moreover, concerns about labor itself are strongly associated with fear of pain at all. Most women are aware of pain during labor, but they expect that it should be soothed with currently available methods, ensuring safety for the mother and the child. In this paper pharmacological methods of labor pain relief, including inhaled analgesia, opioid analgesics, non-opioid drugs, pudendal nerve block and epidural anesthesia were described.